The wish [compact disc, unabridged] - Sparks, Nicholas (Hachette Audio, 2021)
A successful travel photographer, Maggie Dawes, struggling to come to terms with a sobering medical diagnosis, is unexpectedly grounded over Christmas with her young assistant and begins to tell him the story of the love that set her on a course she never could have imagined.